1997
DOI: 10.1080/09629359791839
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine changes in patients with heatstroke during pilgrimage to Makkah

Abstract: Circulating levels and role of IL-6, IL-1ra, TNFsr-II and CRP in patients with heatstroke is not fully known. This study correlated levels of these mediators with outcome in 26 patients. In survivors (n=20), IL-6 concentration declined on cooling, whereas in non-survivors levels continued to increase at 6 h following admission before declining. Admission TNFsr-II concentrations in survivors were significantly lower than non-survivors and levels continued to rise in both groups. IL-1ra levels were markedly elev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
55
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(56 citation statements)
references
References 17 publications
1
55
0
Order By: Relevance
“…Although IL-6 concentrations at admission were not significantly different between survivors and non-survivors, 36 differences became significant at .6 h following admission. Interestingly, the extent of cytokine response correlated with outcome, where sustained high concentrations despite body cooling were associated with poor outcome.…”
Section: Cytokinesmentioning
confidence: 94%
See 3 more Smart Citations
“…Although IL-6 concentrations at admission were not significantly different between survivors and non-survivors, 36 differences became significant at .6 h following admission. Interestingly, the extent of cytokine response correlated with outcome, where sustained high concentrations despite body cooling were associated with poor outcome.…”
Section: Cytokinesmentioning
confidence: 94%
“…IL-6 did not rise significantly until the hyperthermic phase and remained elevated at 24 h of recovery. 42,43 Although it has been shown that high IL-6 levels correlate with heatstroke morbidity and mortality, 36,37 evidence for what would be an expected protective effect of neutralizing IL-6 is not available. Elevated cytokine modulators, i.e.…”
Section: Cytokinesmentioning
confidence: 99%
See 2 more Smart Citations
“…During prolonged heat exposure, autonomic mechanisms of thermoregulatory control, such as sweating may become exhausted, resulting in dramatic increases in T c with values as high as ∼47°C reported in patients (Bouchama et al, 1991;1993;Chang, 1993;Hammami et al, 1997;Hashim et al, 1997;Lu et al, 2004;Sonna et al, 2004). Hypothermia (∼ 7°C below baseline) and fever (∼ 1-2°C above baseline) are long-term heat stroke recovery responses that are less well-recognized, but are thought to be a consequence of the systemic inflammatory response (SIRS) that occurs in response to endotoxin leakage from the ischemic GI tract (Attia et al, 1983;Austin and Berry, 1956;Leon et al, 2005;Malamud et al, 1946;Romanovsky and Blatteis, 1996;Wilkinson et al, 1988;Wright, 1976).…”
Section: Physiological Responses To Heat Stressmentioning
confidence: 99%